Sensitive and Selective Detection of Multiple Metal Ions Using Amino Acids Modified Glassy Carbon Electrodes. Issue 3 (8th February 2018) - Nisar, Anum; Shah, Afzal; Zahid, Anum; Iftikhar, Faiza Jan; Hassan, Abbas; Shah, Aamir Hassan; She, Zhe; Akhter, Mohammad Salim; Piro, Benoit; Kraatz, Heinz-Bernhard
Abstract : We report for the first time the electrochemical detection of Zn 2+, Cd 2+, Cu 2+ and Hg 2+ at the surface of modified glassy carbon electrodes with different amino acids. The designed sensors showed superior heavy metal ion (HMs) detection limits, which are at lower levels than the thresholds suggested by the World Health Organization. The influence of the concentration of the modifier, pH, accumulation time, deposition potential and supporting electrolytes were tested for achieving the best sensing response of the analytes. The sensors demonstrated remarkable electrocatalytic activity and excellent discrimination ability for the target analytes in the presence of 200-fold higher concentration of interfering agents. Glycine was found to have the best HMs chelation ability among all the eight natural amino acids tested experimentally in this work. Theoretical DFT-based computational calculations supported the experimental results of HM-amino acid interaction. Thus, this work not only reports sensors with enhanced detection capability for HMs but also provides useful insights toward future designing of water filters containing amino acids-based materials for metal sequestration.